Pengaruh Teknik Relaksasi Otot Progresif Terhadap Tingkat Stres Pada Mahasiswa Tingkat Akhir Program Studi (S-1) Keperawatan Dalam Menyusun Skripsi Di FITKes UNJANI - Juhaeriah, Juju (JURNAL KESEHATAN KARTIKA, 2022)
Stress is a mental disorder that a person faces due to pressure. This pressure arises from the failure of individuals to meet their needs or desires. Final year students, a group of individuals who are prone to stress. Handling stress can be pharmacological and non-pharmacological, one way to reduce non-pharmacological stress levels is muscle relaxation. Progressive muscle relaxation therapy, namely therapy by providing tension and then relaxing the muscles, the resulting feeling of relaxation is considered to be able to reduce stress levels. This study aims to determine whether or not there is an effect of progressive muscle relaxation techniques on stress levels in final year students of the Bachelor of Nursing student program in compiling their thesis at the FITKes UNJANI. Method : The design of this study used quantitative research. The design used in this study was a Quasi Experiment with a one group pretest-posttest design. The sample in this study was 64 respondents. Result and Conslusion: The results showed that the stress level of the respondents before the intervention was given was in the category of moderate stress (46.9%) and severe stress (53.1%). After being given the intervention, they were in the category of mild stress (65.6%) and moderate stress (34.4%). Wilcoxon test results are known Asymp. Sigh. (2-tailed) is worth 0.000. Because the value of 0.000 is less than <0.05, so there is an effect of progressive muscle relaxation techniques on reducing stress in final year students in compiling a thesis at the Faculty of Social Sciences Unjani Cimahi. The conclusion of the study is that there is a decrease in stress levels in final year students by administering progressive muscle relaxation therapy